Development of Intercity EMUs Brake System - ZHANG Liguo; WANG Xiaodong; WANG Jiexian; LIU Haibo; HE Danlu (机车电传动)
The braking system design proposal on CRH6 intercity EMUs was introduced. According to the transport demand, the difficulty for development of the braking system was analyzed, and the top design indexes for braking system were indentified. Also, the component, the control, the safety guarantee, the deceleration define, empty and load adjustment, and etc of the braking system were illustrated, and the validation was introduced according to the calculation and routine test.